2021
DOI: 10.3390/jcm10204646
|View full text |Cite
|
Sign up to set email alerts
|

The Prolonged Diagnostic Pathway of Young Adults (Aged 25–39) with Cancer in the United Kingdom: Results from the Young Adult Cancer Patient Journey Study

Abstract: Purpose: Teenagers and young adults (TYAs; aged 13–24) experience prolonged intervals to cancer diagnosis. Insight into diagnostic intervals in young adults (YAs; aged 25–39) and subgroups at risk for long intervals is lacking. We investigated the diagnostic pathway of YA cancer patients, examined patient and tumor characteristics associated with its length, and compared the patient interval length of our sample with a TYA cohort. Methods: In this cross-sectional survey YAs diagnosed with cancer in the UK in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Compared to older individuals, young adults are less likely to have a primary care physician due to the allure of immediate alternatives in their fast-paced lives, such as their smartphones, walk-in clinics [41] or pharmacies [42]. Soomers et al (2021) found that among 341 young adults, more than 3 months passed from the onset of symptoms to the first medical consultation in 21% of cancer cases of different etiologies [43].…”
Section: Nanobiosensors-sensing Mechanism and Attributesmentioning
confidence: 99%
“…Compared to older individuals, young adults are less likely to have a primary care physician due to the allure of immediate alternatives in their fast-paced lives, such as their smartphones, walk-in clinics [41] or pharmacies [42]. Soomers et al (2021) found that among 341 young adults, more than 3 months passed from the onset of symptoms to the first medical consultation in 21% of cancer cases of different etiologies [43].…”
Section: Nanobiosensors-sensing Mechanism and Attributesmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) recommends that adults with symptoms suggestive of sarcoma should be referred to specialists for further assessment within 2 weeks. For children and young people (those under 25 years), referral should be made within 48 hours [9,10]. However, the heterogeneity and ambiguity of symptoms that may be indicative of sarcoma often result in patients experiencing longer times to referral for specialist tests and diagnosis compared with more common cancers [4,11].…”
Section: Introductionmentioning
confidence: 99%